TRANSFORMASI PERPUSTAKAAN BERBASIS INKLUSI SOSIAL DI DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN KARANGANYAR - Aprilia Puspita Wardani; Salsabilla Nathania Arumsari; Mega Alif Marintan (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
This study aims to analyze the social inclusion program managed by the Karanganyar Archives and Library Office (Disarpus). The social inclusion program in libraries is designed to improve the quality of life of the community, increase welfare, encourage creativity, and reduce various information access gaps. The research method used in this article is a descriptive qualitative research method with data collection techniques including interviews, netnography, and observation. The results of the study show that the social inclusion library programs implemented by Disarpus Karanganyar are KASUARI (Karanganyar Suka Menari), SERUNDENG (Serunya Mendongeng), KARAMEL (Karanganyar Melukis), ROLASAN (Roadshow Literasi Anak Karanganyar), and Ka'Nofia (Karanganyar Nonton Film Bareng). Through these programs, the library's role as part of an inclusive and empowering non-formal learning environment is strengthened. The presence of this program provides a safe and positive environment for the community to grow and learn together.